2005
DOI: 10.1016/j.jda.2004.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Chaining algorithms for multiple genome comparison

Abstract: Given n fragments from k > 2 genomes, Myers and Miller showed how to find an optimal global chain of colinear non-overlapping fragments in O(n log k n) time and O(n log k−1 n) space. For gap costs in the L 1 -metric, we reduce the time complexity of their algorithm by a factor log 2 n log log n and the space complexity by a factor log n. For the sum-of-pairs gap cost, our algorithm improves the time complexity of their algorithm by a factor log n log log n . A variant of our algorithm finds all significant loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 25 publications
0
102
0
1
Order By: Relevance
“…To investigate this issue, we compared the running times and coverages obtained without (using Chainer [1]) and with proportional overlaps (using Algorithm 1) on 694 pairwise genome comparisons. Our comparison set consists in all pairwise genome comparisons of strains of the same bacteria (intra-species comparisons) as of Jan 2010: it comprises 346 different genomes from 87 species retrieved from Genome Reviews database [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate this issue, we compared the running times and coverages obtained without (using Chainer [1]) and with proportional overlaps (using Algorithm 1) on 694 pairwise genome comparisons. Our comparison set consists in all pairwise genome comparisons of strains of the same bacteria (intra-species comparisons) as of Jan 2010: it comprises 346 different genomes from 87 species retrieved from Genome Reviews database [5].…”
Section: Resultsmentioning
confidence: 99%
“…Given the set of n shared genomic intervals, i.e. fragments, the Maximum Weighted Chain problem (MWC) is solved in O(n log n) time by dynamic programming when overlaps between adjacent fragments are forbidden [10,1]. Alternatively, Felsner et al showed that this problem is a special case of the Maximum Weighted Independent Set problem in a trapezoid graph, which they solve by a sweep line algorithm over an equivalent box order representation of the graph [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chaining techniques used in [Abouelhoda and Ohlebusch 2005;Höhl et al 2002] to compute the heaviest chain are based on a graph model whose edges, in general, are a subset of the edges in G M . To prune, the authors exploit geometrical properties of their graph model, as well as a priority queue-based pruning technique.…”
Section: Similar Techniquesmentioning
confidence: 99%
“…Trapezoid graphs are applied in various fields, including modeling channel routing problems in VLSI design [6] and identifying the optimal chain of non-overlapping fragments in bioinformatics [1]. Trapezoid graphs were first investigated in [4,6].…”
Section: Introductionmentioning
confidence: 99%